Kajian Potensi Pengembangan Investasi Di Kabupaten Brebes - Kurniawan; Kodir; Ardiansyah, Aqib; Sutarmin (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2018)
One of the efforts to increase economic development is to increase investment activities inall business sectors in Brebes District, infrastructure support that supports investment becomesan important factor to increase investment. The existence of investment profile becomes the maininformation about the potential of investment development through investment in Brebes Regency.The objective of the research is to provide information about the potential of investment inBrebes Regency by region and by economic sector. Providing information on infrastructure andinfrastructure supporting investment in Brebes Regency. Using quantitative descriptive analysis.The results of the research indicate that potential sectors that are potential to be developed inBrebes district potential sectors to be developed include agriculture, forestry and fisheries withhorticultural crops, manufacturing and large and retail trade sectors; car and motorcyclerepairs with onion, chilli, potato, mushroom, carrot, tofu, cracker, salted egg, soft drinks andbottled water.